A guide to the consumer price index. - Australian Bureau of Statistics ([Canberra] : Australian Bureau of Statistics, 1999)
A booklet designed to promote understanding of the CPI among general users. Briefly covers such topics as: what is the CPI; to whom does the CPI relate; the composition of the CPI "basket"; collecting the prices; how the CPI is calculated; and using the CPI. Also contains a table showing the weighting pattern of the 13th CPI and examples of the items priced for the CPI.
Catalogue no. 6440.0
Keywords: Consumer price indexes -- Australia -- Handbooks, manuals, etc; Cost and standard of living -- Australia -- Handbooks, manuals, etc